q-Szász operators which preserve x 2 - Mahmudov, Nazim I. (Springer Verlag, 2013)
In the present paper we construct q-Szász operators that preserve the third test function e 2. Rate of global convergence is obtained in the frame of weighted spaces. Furthermore, we obtain a Voronovskaja type theorem for these operators.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: modulus of continuity, q-Szász-Mirakjan operators, Voronovskaja type theorem